Vibrational response of complex structures to high-frequency correlated loads - Finn, Joshua (2025)
Distributed Electric Propulsion (DEP) is an innovative aircraft concept where thrust is generated by an array of electrically powered propellers. The application of electric propulsion systems ensures that a significant proportion of the cabin noise within DEP aircraft is the result of structural vibrations driven by Turbulent Boundary Layer (TBL) effects. The purpose of this thesis is thus to extend the Dynamical Energy Analysis (DEA) approach to consider excitations by high frequency correlated pressure fields, such as the TBL pressure field.